Evaluation of oil extraction by ultrasonication of chlorella vulgaris grown in nitrogen, phosphorous, and potassium (NPK) - Reynoso, Ryan Leong
Microalgae can be processed to produce a variety of biofuels. However, microalgae culture presents challenges due to the high cost of current methods. To minimize the cost, commercially available, inexpensive medium, chemical fertilizer 14:14:14 nitrogen, phosphorus, and potassium (NPK) is utilized as the growth medium. The extraction of oil via ultrasonication of the microalgae Chorella vulgaris grwon in NPKK is investigated. NPK in about 8 1 distilled water per batch is used at 28 ± 2̊C with 12 h light and 12 h dark photoperiod and 1,500 lux light intensity. The microalgae are then harvested during the exponential growth phase. Ultrasonic-assisted extraction of the samples, utilizing chloroform:methanol (2:1) solvent at different temperatures and contact time is performed. The analysis of the extracts demonstrates that ultrasonification at 1 h contact time and 60̊C produces the highest oil yield at an average of 17.26%. Furthermore, the results reveal that NPK can support the growth of C. vulgaris; thereby providing a more economical growth medium. Statistical test show that ultrasonic time and temperature have significant effect on the amount of oil that can be extracted from the algae samples.